Tracing a Colonial Enterprise through Colonial Archives: Reconstructing the History of Michiels–Arnold Landen (1887–1942) - Ismawarno, Agung; Singgih Tri Sulistiyono; Yety Rochwulaningsih; Haryono Rinardi (Universitas Islam Negeri Raden Intan Lampung, 2026)
Research on colonial enterprises has generally emphasized economic performance while paying limited attention to colonial archives as products of power relations and to collective memory as complementary historical evidence. This study reconstructs the history of Michiels–Arnold Landen (MAL), a colonial plantation company operating in the Dutch East Indies from 1887 to 1942, by integrating critical archival analysis with collective memory. Using the historical method, the study examines company reports, financial statements, shareholders’ meeting minutes, colonial newspapers, government records, historical maps, and oral testimonies collected through field observation. The findings demonstrate that MAL evolved through organizational restructuring, commodity diversification, territorial expansion, and administrative modernization, reflecting its integration into the broader structure of colonial capitalism. The study further argues that colonial archives were not merely repositories of factual information but also instruments that represented corporate legitimacy, administrative order, and colonial authority while marginalizing agrarian conflicts and local experiences. Collective memory preserved by communities in Cileungsi, Cibarusa, Jonggol, and surrounding areas complements and verifies archival evidence by preserving the spatial and social traces of the former plantation landscape. By combining colonial archives with collective memory, this study contributes to the historiography of colonial business history and demonstrates that corporate history can be more comprehensively reconstructed through the integration of documentary and community-based historical sources.